Diversity of arbuscular mycorrhizal fungi in Brazil’s Caatinga and experimental agroecosystems - Pontes, J.S.; Oehl, F.; Marinho, F.; Coyne, Danny L.; Silva, D.K.A. da; Yano-Melo, A.M.; Maia, L.C. (Wiley, 2017)
Striga hermonthica is a serious parasite of cereals in most of the semi-arid savanna zone of West Africa, causing substantial yield loss. It has been observed that some soybean cultivars are capable of stimulating germination of S. hermonthica seed, which would reduce the seed bank in the soil. This study was undertaken to quantify the effect of a soybean crop (compared with a sorghum control) on S. hermonthica emergence in subsequent maize in three farmers' fields in northern Nigeria. Soybean cultivar TGx 1740-7F, previously identified as efficacious for S. hermonthica seed germination, was grown at four densities without P fertilizer to test the effect of increasing plant density of soybean on subsequent S. hermonthica parasitism. The effect of P as single super phosphate was tested on the two highest soybean densities. S. hermonthica parasitism on maize was significantly lower after unfertilized soybean than after the sorghum control treatment at two of three trial sites. Soybean rotation increased maize yield by approximately 90% for the three sites combined. Increasing soybean plant density did not result in lower emerged S. hermonthica. Application of P to soybean at the higher soybean densities resulted in higher root length density, lower emerged S. hermonthica on maize (P<0.15), and significantly higher maize yield. The results suggest that an efficacious cultivar of soybean reduces S. hermonthica parasitism on a succeeding maize crop and that the effect is increased by application of P to the soybean.